Physics Learning Media Based on Social Media: STEM-Based Videos on Renewable Energy through TikTok Application (Jurnal Pendidikan Fisika, 2026)
The integration of digital technology into senior high school physics teaching is becoming more urgent to support students’ engagement and understanding of abstract concepts, especially in time-limited classroom settings. TikTok, as a short-form video platform with strong visual and audiovisual features, offers potential to deliver brief, interactive learning content aligned with students’ digital habits. This study aimed to create STEM-based learning videos on renewable energy topics through TikTok and to evaluate their feasibility and appeal as teaching tools. The study used a Research and Development (R&D) approach, employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), and was conducted at SMA Islam Elsyihab Bandar Lampung. Product feasibility was assessed by four validators two media experts and two content experts while user responses were gathered from a physics teacher and 37 students via questionnaires. The results show that the videos are highly feasible: media expert validation averaged 90%, and content expert validation averaged 84%, both classified as very feasible. User evaluations also demonstrated strong acceptance; the teacher rated the videos as 96% (very interesting), and student responses averaged 92% (very interesting), indicating high perceived attractiveness and educational support. The novelty of this study lies in combining a STEM instructional design with TikTok short videos on renewable energy physics, supported by a systematic ADDIE development process and tested by multiple stakeholders for feasibility and appeal. In conclusion, STEM-focused TikTok learning videos are feasible, engaging, and accessible digital resources that can supplement traditional instruction and promote student-centered learning in senior high school physics. This study advances physics education by offering a validated model for utilizing popular social media platforms to deliver structured STEM content and boost engagement through technology-rich learning environments.
Keywords: ADDIE model; digital learning; STEM education; renewable energy; TikTok education